2013
DOI: 10.1002/cncr.28416
|View full text |Cite
|
Sign up to set email alerts
|

Sex disparities in diagnosis of bladder cancer after initial presentation with hematuria: A nationwide claims‐based investigation

Abstract: Background Women have disproportionately higher mortality rates relative to incidence for bladder cancer. Multiple etiologies have been proposed, including delayed diagnosis and treatment. Guidelines recommend rule-out of malignancy in men and women presenting with hematuria. We aimed to determine the difference in timing from presentation with hematuria to diagnosis of bladder cancer in women versus men. Methods This is a retrospective population-based study examining the timing from presentation with hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
105
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 33 publications
9
105
1
3
Order By: Relevance
“…Die auch aus internationalen Daten bekannten Geschlechterunterschiede bei der Stadienverteilung bzw. bei den Überle-bensraten werden unter anderem durch eine mögliche Verzögerung der Diagnostik bei Frauen sowie hormon-und genetisch bedingte Unterschiede der Tumorbiologie begründet [14,15].…”
Section: Diskussion Und Internationale Einordnungunclassified
“…Die auch aus internationalen Daten bekannten Geschlechterunterschiede bei der Stadienverteilung bzw. bei den Überle-bensraten werden unter anderem durch eine mögliche Verzögerung der Diagnostik bei Frauen sowie hormon-und genetisch bedingte Unterschiede der Tumorbiologie begründet [14,15].…”
Section: Diskussion Und Internationale Einordnungunclassified
“…In this group, men were twice as likely to be referred within a month of their hematuria compared to women (36 vs. 17%). A retrospective review of MarketScan databases for hematuria also demonstrated a significant delay to diagnosis in women who were more likely to experience a delay greater than 6 months (17.3 vs. 14.1%, p < 0.001) [11]. …”
Section: Are There Gender Differences In Referral Patterns?mentioning
confidence: 99%
“…The 6-month time frame was chosen based on the established literature, with delays longer than 6 months being associated with adverse outcomes. 12,13 Secondary endpoints included provider contribution to the hematuria evaluation by type and utility of the hematuria evaluation. Medicare specialty codes were used to determine whether the subject was seen by a urologist (Medicare specialty code 34), and whether the urologist performed one of the relevant procedures in the 6 months after hematuria diagnosis.…”
Section: Discussionmentioning
confidence: 99%